Desire Work: Producing Heterosexuality in South African Pentecostal Gay Men. Issue 3 (26th May 2016) - Hackman, Melissa
ABSTRACT: Gay men in Cape Town, South Africa joined a Pentecostal ministry in an attempt to produce what they understood as 'natural' heterosexual attraction. In this article, I explore how these gay men try to form new selves through what I call 'desire work', or physical and emotional micropractices and discipline. Desire is not 'natural', but it is produced through a multitude of engagements with cultural norms, public life, political economies, and social forces. New selves are built through concerted bodily changes and comportment [Mahmood, Saba. 2005. Politics of Piety: The Islamic Revival and the Feminist Subject . Princeton, NJ: Princeton University Press], and although gay Pentecostal men shared this process, their success was limited. I understand desire work as a response to a larger context in which many Pentecostals are disaffected with the post-apartheid government and withdraw from politics as a result. Their fears of the uncertainties of democracy pushed them to engage in optimistic fantasies of heterosexual lives, which were not often realised [Berlant, Lauren Gail. 2011. Cruel Optimism . Durham, NC: Duke University Press].